In Silico Investigation of pH-Dependence of Prolactin and Human Growth Hormone Binding to Human Prolactin Receptor (Communications in Computational Physics, 2013)
Experimental data shows that the binding of human prolactin (hPRL) to human prolactin receptor (hPRLr-ECD) is strongly pH-dependent, while the binding ofthe same receptor to human growth hormone (hGH) is pH-independent. Here wecarry in silico analysis of the molecular effects causing such a difference and reveal therole of individual amino acids. It is shown that the computational modeling correctlypredicts experimentally determined pKa's of histidine residues in an unbound statein the majority of the cases and the pH-dependence of the binding free energy. Structural analysis carried in conjunction with calculated pH-dependence of the bindingrevealed that the main reason for pH-dependence of the binding of hPRL-hPRLr-ECDis a number of salt-bridges across the interface of the complex, while no salt-bridges areformed in the hGH-hPRlr-ECD. Specifically, most of the salt-bridges involve histidineresidues and this is the reason for the pH-dependence across a physiological range ofpH. The analysis not only revealed the molecular mechanism of the pH-dependenceof the hPRL-hPRLr-ECD, but also provided critical insight into the underlying physic-chemical mechanism.